Crowdfunding, Financing Constraints, and Real Effects - Kumar, Praveen; Langberg, Nisan; Zvilichovsky, David (Management Science, 2020)
We study the feasibility and optimal design of presale crowdfunding contracts where participating consumers pay a premium above the future expected spot price and financially constrained entrepreneurs balance the potential product–market distortions introduced through presale crowdfunding against the cost of traditional external financing. Our analysis shows how such crowdfunding contracts enable the execution of projects that could not be otherwise undertaken and highlights novel interactions between the cost of capital, demand uncertainty, and production. Tighter financing constraints reduce the ability of the monopolist to extract surplus but, contrary to the usual result, may increase production. We evaluate how uncertainty and market size reduce the price-discriminating power of the monopolist and affect the optimal contract regime. Nevertheless, we show how such presale price-discriminating contracts are implementable even when the number of potential consumers is relatively high and their individual demand is stochastic. This paper was accepted by Gustavo Manso, finance.